Reforming Justice for Digital Sexual Violence in Southeast Asia: Indonesia’s Legal Protection Framework and Regional Lessons - Maskun; Muhammad Mutawalli Mukhlis; M. Aris Munandar; Syamsuddin Muchtar; Nur Azisa; Audyna Mayasari Muin; Arnita Pratiwi Arifin; Budiyanto (Universitas Negeri Semarang, 2026)
Digital sexual violence is escalating in Southeast Asia as social media, chat services, and cloud storage enable non-consensual recording, dissemination of intimate images, sexual threats, and technology-facilitated harassment. This article assesses Indonesia’s legal protection framework and draws regional lessons for reform. Using normative legal research with international human rights law and comparative legal study as its primary approaches, this article examines Indonesia’s criminal law policies and selected judicial decisions concerning electronic-based sexual violence under the Sexual Violence Criminal Acts Law (SVCA Law, Law No. 12/2022) and the Electronic Information and Transactions Law (EIT Law, Law No. 19/2016). The analysis finds that Indonesia has advanced by criminalizing electronic-based sexual violence under the SVCA Law, yet sanctions remain focused on imprisonment and fines, leaving gaps for effective deterrence when offenders repeatedly exploit online communication tools. A recent revenge-porn case illustrates judicial experimentation with internet-access restrictions and the countervailing legality principle. Comparative insights from Canada and Germany show that court-supervised digital restrictions can be structured as additional penalties, while regional experiences in Malaysia, Thailand, and Japan underscore the value of conduct-specific offences and safeguards. The article proposes amending the SVCA Law, as lex specialis, to authorize proportionate revocation or limitation of online-communication access, supported by clear criteria, review mechanisms, and consistent inter-agency monitoring to balance constitutional freedoms and human rights.